Cocoa fermentation: Microbial identification by MALDI-TOF MS, and sensory evaluation of produced chocolate. (April 2017) - Miguel, Maria Gabriela da Cruz Pedrozo; Reis, Livia Viana de Castro; Efraim, Priscila; Santos, Cledir; Lima, Nelson; Schwan, Rosane Freitas
Abstract: Dynamic microbial over the cocoa fermentation using starter culture and the effect sensory characteristics of chocolate produced were investigated. The cocoa fermentation inoculated with Saccharomyces cerevisiae CCMA0681 and Lactobacillus fermentum UFLA CHBB 8.12 as starter cultures were assessed, and compared with spontaneous fermentation. The microbial succession was identified using polyphasic approach including classical morphological and biochemical assays, and Matrix Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF). Overall 873 colonies were isolated, 445 (51%) strains were isolated from the spontaneous fermentation, while 428 (49%) strains were isolated from the inoculated fermentation. The dominant yeast in both fermentation processes were S. cerevisiae and Candida magnolia . L. fermentum and Pediococcus acidilactici were detected in both fermentations, whereas L. coryniformis, L. curvatus, L. mali, L. plantarum, and L. sakei were isolated from the spontaneous fermentation only. Acinetobacter sp., Gluconobacter oxydans, and Acetobacter pasteurianus were isolated from both the fermentation processes. Chocolate produced from the spontaneous fermentative process presented dominance of the bitter flavour, while obtained through inoculated fermentation process presented bitter, astringent and acid as dominant flavours. Cocoa inoculation with S. cerevisiae and L. fermentum affected the sensory quality of the produced chocolate. The microbial inoculation influenced on fermentation and therefore the final product. Highlights: Good chocolates were produced using starter cultures of lactobacillus and yeast. MALDI-TOF MS was effective at identifying different microbial species. The chocolate bitter sensation was predominant in inoculated cocoa beans. The dominant yeast were S. cerevisiae and Candida magnolia .